High voltage gain resonant DC-DC converter with vm cells for renewable sources applications - Hasanzadeh Saeed; Salehi Seyed Mohsen; Najafi Ehsan; Horri Farinaz (Serbian Journal of Electrical Engineering, 2022)
Due to the widespread impact of renewable energy resources on high power density grids, transmission at the DC regime has been considered more useful than AC transmission systems. The findings of this study suggest the application of a ripple-free input current resonant DC-DC converter possessing high voltage gain and high efficiency as being more suitable for renewable energy systems. Applying variable switching frequency control systems, the proposed converter discussed here is generally operated at the critical conduction mode for soft switching of the semiconductor switches. Using the resonance mechanism, the proposed converter causes a decrease in the turn-on loss of the power switch without needing additional semiconductor gadgets. It leads to a reduction in the reverse-recovery losses of the rectifying diodes. Also, analysis and design consideration of the proposed converter are presented with excellent performance.